An alternative approach to evaluating the energetic carrying capacity of the landscape for Mallard Anas platyrhynchos wintering in the Mississippi Alluvial Valley, USA - Boudreau, Melanie R.; Lancaster, Joseph D.; Adjaye, Daniela F.; Dentinger, Jane E.; Dolan Todt, Lacy A.; Ripa, Gabrielle N.; Ramirez-Reyes, Carlos; Sklarczyk, Craig A.; Thornton, Bradly S.; Todaro, Holly M.; Kaminski, Richard M.; Davis, J. Brian (Wildfowl, 2024)
Habitat conservation planning for wintering waterfowl in North America uses estimates of waterfowl energy requirements to assess the ability of regional landscapes to support populations. However, because the spatial and temporal configuration of resources can influence an individual animal’s use of the landscape, there may be benefits to considering the availability of energy from food within individual home ranges on developing conservation planning. This possibility was investigated for female Mallard Anas platyrhynchos wintering in the Mississippi Alluvial Valley using: (1) published energy values for different landcover types (quantified as duck energy days; DEDs/ha), (2) maps of landcover and water availability, and (3) winter home range estimates created using location data from 128 birds fitted with VHF radio transmitters. Following current methods used for regional assessments of food resources available for birds, landcover types were first transformed into their corresponding DED values, and the amount of energy considered potentially accessible to Mallard within their home ranges was then limited by accounting for water availability and DED decay rates. Relatively energy-rich landcover types, such as moist-soil wetlands and croplands, were less likely to be accessible given water coverage. Moreover, a large proportion of Mallard locations were in areas that provided no apparent energy value. Most (> 90%), but not all, Mallard home ranges surpassed the birds’ minimum winter energy needs (i.e. 123 DEDs). We suggest that waterfowl habitat conservation planning should consider an individual bird, home-range approach for DED assessments, and use those assessments to: (1) begin examining potential gaps in landscape water coverage, (2) ensure that multiple resource patches are accessible to individual birds, and (3) provide the mixture of landcover types (including those used for other life history needs), required by focal waterfowl species.